Cuvânt la redeschidere - Nicolae Mecu (Revista de Istorie și Teorie Literară)
This article reopens The Edition Chronicle Column. I review the editing of the classical Romanian writers after 1989, and address discussion about the requirements of that work in the present times, timeframe without ideological pressures and censorship. In the second part of the article I am revealing my opinion about the norms and the needs for the editing on one hand, the status of the editor in our cultural times on the other.